ASSOCIATION BETWEEN HAND-HELD DYNAMOMETER MEASURES OF HAMSTRING STRENGTH AND FORCE OBTAINED FROM THE NORDIC HAMSTRING EXERCISE. Issue 4 (1st February 2017) - Evans, Kate; Williams, Morgan
Abstract : Background: The Nordic hamstring exercise (NHE) is included in many injury prevention programmes. Recently, a device that measures force at both ankles during the NHE has been introduced to help monitor and track an athlete's progress. Understanding the association between different hamstring strength protocols may reveal a better understanding of the NHE as an assessment and help practitioners to decide on its application. Objective: To explore the associations between a series of hamstring strength measures obtained from a hand-held dynamometer with the force obtained during a NHE. Design: This cross-sectional study involved participants being measured during a single session. Associations between all individual measures were assessed. In addition, the combined effect of the hand-held measures to predict Nordic eccentric strength (NES) were explored. Setting: Professional team sports. Patients (or Participants): Seventy-nine professional male team sport athletes. Main Outcome Measurements: NES obtained from a commercial device. Hand held dynamometry break assessments of hip extension (HE), hamstring inner range strength (HI) and hamstring strength at 30° knee flexion (H30). Results: Based on the univariate correlations between variables (preferred limb only), the smallest association was between NES and HE (r 2 =0.02) and the largest association between NES and HI (r 2 =0.26). Using multiple regression, HI (P=0.0001) and H30 (P=0.0083) predicted NES (r 2 =0.32; RMSE=64N; P<0.0001). The model was not improved with the addition of HE (r 2 =0.33; RMSE=64N; P<0.0001). Conclusions: Each hamstring strength assessment may offer unique information about the current hamstring strength quality of an athlete. Despite, HI having the largest effect, and the improved model with the addition of H30, handheld dynamometry replacing the using these measures in place of NES obtained from a commercial device is not advised.